DESIGNING A MOBILE APPLICATION MISIBEASISWA FOR CONNECTING SPONSORS WITH UNDERPRIVILEGED YOUTH FOR EDUCATIONAL CONTINUITY - Istiana Khaerunisa; Puan Mahara; Nur Syabila Rosa; Dhieka Avrilia Lantana (Cirebon International Conference on Education and Economics Proceeding, 2024)
Nowadays, many people believe that education is a crucial pathway to a brighter future. However, financial constraints prevent numerous talented and motivated young individuals from pursuing higher education. To address this issue, crowdfunding implemented through an innovative mobile app called Misi Beasiswa has been developed to bridge the gap between financially struggling youth and potential sponsors. Sponsors can get in touch with deserving students through this mobile app so that they could help them accomplish their educational goals. Misi Beasiswa not only facilitates connections between sponsors and students but also fosters relationships within university. University ensure transparency and accountability by regularly posting academic results and associated expenses per semester. The technique used to develop Misibeasiswa was design thinking which is defined as a creative way of solving problems by putting people first. Design thinking involves finding out what users need most, what challenges they face and what would make their experience better. Therefore Misi Beasiswa adopted this approach in order to create user-friendly environment that supports meaningful educational connections capable of transforming lives.